2011
DOI: 10.1063/1.3615821
|View full text |Cite
|
Sign up to set email alerts
|

Probing the physiology of ASH neuron in Caenorhabditis elegans using electric current stimulation

Abstract: Electrical stimulation has been widely used to modulate and study the in vitro and in vivo functionality of the nervous system. Here, we characterized the effect of electrical stimulation on ASH neuron in Caenorhabditis elegans and employed it to probe the neuron's age dependent properties. We utilized an automated microfluidic-based platform and characterized the ASH neuronal activity in response to an electric current applied to the worm's body. The electrically induced ASH neuronal response was observed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…28 Various microfluidic devices have been reported that trap multiple animals for high-throughput imaging, 29 automated sorting, 30 quantification of muscular forces, 31 chemosensory analyses, 25,32 electrotaxis, 33,34 thermosensory analyses, 35,36 and whole-animal stress responses. 24,37 A long term culture platform for C. elegans based on microfluidic approaches has also been presented.…”
Section: Introductionmentioning
confidence: 99%
“…28 Various microfluidic devices have been reported that trap multiple animals for high-throughput imaging, 29 automated sorting, 30 quantification of muscular forces, 31 chemosensory analyses, 25,32 electrotaxis, 33,34 thermosensory analyses, 35,36 and whole-animal stress responses. 24,37 A long term culture platform for C. elegans based on microfluidic approaches has also been presented.…”
Section: Introductionmentioning
confidence: 99%
“…Using a microfluidic chip21, we delivered a hyperosmotic stimulus (glycerol) to the worm’s nose and recorded Ca 2+ transients from the ASH sensory neuron. We chose ASH, the well-studied worms’ main nociceptor2122232425262728, because it can be activated by a wide range of repellents252930, thus being especially significant for C. elegans survival and environmental perception.…”
mentioning
confidence: 99%
“…Combined with fluorescence imaging of calcium transmitters and neurons, behavior mechanism could be explored in the neuronal level [60]. Based on the established microfluidic devices by several researchers, accurate stimuli could be delivered to individual worms flexibly and responses of worms behavior and neuron could be monitored [33,35,39,52,[61][62][63][64].…”
Section: Neuron Activitymentioning
confidence: 99%